Um estudo a respeito da generalização de padrões nos livros didáticos de Matemática do Ensino Fundamental - Carmo, Paulo Ferreira do (2014)
The study of algebra is extremely important in basic education, because it enlarges the ability of our students in solving mathematical problems or other areas of knowledge. Several studies (PONTE 2005; SESSA, 2005; BRANCO, 2008; VALE et al., 2008) have shown that basic education students have many difficulties when using the algebraic language to express ideas and solve problems. The objective of this research was to examine whether the textbooks of Mathematics in Secondary School chosen PNLD/2011 introduce algebraic language through generalization activities and standards as it occurs. As a theoretical framework, we use Fiorentini´s; Miorin´s; Miguel´s (1993); Fiorentini´s; Fernandes´s; Cristóvão´s (2005), Sessa´s (2005) and Ursini et al.´s (2005) ideas. The research methodology used was content analysis developed by Bardin (2011), to analyze the generalization of the textbooks selected standards activities, the categories were used for the development of algebraic thinking adapted by Hamazaki (2010). As a result of research, it was found that, of the four collections of textbooks analyzed, three use patterns of generalization activities to introduce the algebraic language and, of these three, only one employs four types of generalization of patterns that categorize activities. These activities predominated of figural patterns in a single collection, showing that this type of activity is being underutilized for introducing algebraic language, although several surveys and official documents show the potential of this type of activity for the initiation of the study of algebra